The interfaces of social vulnerability of immigrants and refugees in front of Covid-19: : Mato-grossense scenario - Pellizari, Kelly; Alves, Henrique Roriz Aarestrup (Faculdade de Ciências e Letras - Unesp - Araraquara., 2021)
The objective of this study is to assess the impacts of the Covid-19 pandemic on the immigrant and refugee population in Mato Grosso. The situation of social vulnerability has been aggravated by the increase in social inequalities during the pandemic. Mato Grosso, where the fallacy of a “rich agricultural state” is not a reality for everyone, has seen a considerable increase in immigrants in the last decade, which, when trying to insert itself socially, faces the most varied challenges. The methodological paths are inscribed in the qualitative perspective; using the snowball method, data were collected from 30 immigrants and refugees, who underwent a content analysis with an interpretive bias – not limited to just the statements. The main results indicate that the pandemic intensified the situation of social vulnerability of immigrants and refugees in Mato Grosso, and that social vulnerability has different interfaces, such as: economic, health, legal, psychological, among others not explored in the study.